Antisense oligonucleotide and thyroid hormone conjugates for obesity treatment - Cao, Yang; Matsubara, Tomoko; Zhao, Can; Gao, Wei; Peng, Linxiu; Shan, Jinjun; Liu, Zhengxia; Yuan, Fang; Tang, Lingyi; Li, Peixin; Guan, Zhibin; Fang, Zhuyuan; et al. (My University, 2017)
Using the principle of antibody-drug conjugates that deliver highly potent cytotoxic agents to cancer cells for cancer therapy, we here report the synthesis of antisense-oligonucleotides (ASO) and thyroid hormone T3 conjugates for obesity treatment. ASOs primarily target fat and liver with poor penetrance to other organs. Pharmacological T3 treatment increases energy expenditure and causes weight loss, but is contraindicated for obesity treatment due to systemic effects on multiple organs. We hypothesize that ASO-T3 conjugates may knock down target genes and enrich T3 action in fat and liver. Two established ASOs are tested. Nicotinamide N-methyltransferase (NNMT)-ASO prevents diet- induced obesity in mice. Apolipoprotein B (ApoB)-ASO is an FDA approved drug for treating familial hypercholesterolemia. NNMT-ASO and ApoB-ASO are chemically conjugated with T3 using a non- cleavable sulfo-SMCC linker. Both NNMT-ASO-T3 (NAT3) and ApoB-ASO-T3 (AAT3) enhance thyroid hormone receptor activity. Treating obese mice with NAT3 or AAT3 decreases adiposity and increases lean mass. ASO-T3 enhances white fat browning, decreases genes for fatty acid synthesis in liver, and shows limited effects on T3 target genes in heart and muscle. Furthermore, AAT3 augments LDL cholesterol-lowering effects of ApoB-ASO. Therefore, ASO and hormone/drug conjugation may provide a novel strategy for obesity and hyperlipidemia treatment.